Analisis Karakter Cinta Damai dalam Pembelajaran IPA di Lingkungan Belajar SMP Negeri 17 Kota Jambi - Agustian Agustian; Arnida Arnida (SEJ (Science Education Journal), 2018)
The purpose of this study is to analyze the character of the peaceful love of students in science learning in SMP Negeri 17 Kota Jambi. The method applied in this study is quantitative analysis research methods. This research is also descriptive research that describes the existing conditions in reality. In this study, the primary data is data relating to peace-loving attitudes. The data was obtained by distributing questionnaires. The method used is a closed questionnaire. The subjects of this study were 32 students of class VIII B and 35 students of class VIII C. The results of this study indicated that from all the statements that have been provided by SMP Negeri 17 Jambi successfully cultivate character values in the school including one of them is peace-loving attitude.